La participación ciudadana en el Estado de Derecho ecuatoriano. Un análisis constitucional en el marco del pluralismo jurídico - Almache Soto, Emilio José (2026)
The establishment of the Rule of Law as means of social control by a new Political Constitution in Ecuador as from the 2008, has instituted the Council of Citizen Participation and Control from the analysis of public participation, rights, representation, constituent processes, transparency, social control and its regulatory rules as the Fifth Power. Despite this dialectics, political, economic and structural crises occur on periodic basis, due to the degree of cultural and educational lagging, low level of human development and the lack of opportunities that result in a culture of illegality. Citizen participation exists since the State exists. State exists since men organized society where primitive groups were living into tribes, communities and finally, into villages. Democracy provides a historic, controversial, and extremely complex concept such as sovereignty, to which is it linked. As a political form, it has to harmonize the doctrinal principle with the functional structure; it is the subject with the object of power.